2004
DOI: 10.1292/jvms.66.1403
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Interleukin-6 Concentration in Peripheral Blood of Pre- and Post-Partum Dairy Cattle and Its Relationship to Postpartum Reproductive Diseases

Abstract: ABSTRACT. Reproductive diseases after parturition are a serious problem in dairy cattle. It is important to predict postpartum reproducti ve diseases early and to develop prophylaxis. The objectives of this study were to demonstrate changes in the peripheral blood con centration of interleukin-6 (IL-6) before parturition, which was mainly produced by T helper 2 type (Th2) cells, and to investigate a correlation between the IL-6 concentration and the occurrence of the postpartum retained placenta, endometritis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
59
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(77 citation statements)
references
References 26 publications
16
59
1
1
Order By: Relevance
“…Higher concentrations of non-esterified fatty acids (NEFA) induces inflammation in humans (ZHANG et al, 2006;YAQOOB and CALDER, 2007) and animals (DYK et al, 1995;SORDILLO et al, 2009) with the subsequent release of proinflammatory cytokines (interleukins, TNF-α, IFN-γ; KUSHIBIKI, 2011) from macrophages (KOJ, 1998) and other tissues, particularly the liver (BERTONI and TREVISI, 2013). These cytokines act as biomarkers of postpartum reproductive disorders (ISHIKAWA et al, 2004;ISLAM et al, 2013a;ISLAM et al, 2013b). Plasma interleukins (IL-1β and IL-6) were positively correlated with the severity of the inflammation, worse health status and low milk production in the early lactation period (TREVISI et al, 2012;TREVISI et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Higher concentrations of non-esterified fatty acids (NEFA) induces inflammation in humans (ZHANG et al, 2006;YAQOOB and CALDER, 2007) and animals (DYK et al, 1995;SORDILLO et al, 2009) with the subsequent release of proinflammatory cytokines (interleukins, TNF-α, IFN-γ; KUSHIBIKI, 2011) from macrophages (KOJ, 1998) and other tissues, particularly the liver (BERTONI and TREVISI, 2013). These cytokines act as biomarkers of postpartum reproductive disorders (ISHIKAWA et al, 2004;ISLAM et al, 2013a;ISLAM et al, 2013b). Plasma interleukins (IL-1β and IL-6) were positively correlated with the severity of the inflammation, worse health status and low milk production in the early lactation period (TREVISI et al, 2012;TREVISI et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The IgG exceeded twice the upper level of immunoglobulins in healthy precolostral calves (Sawyer et al 1973). It is difficult to interpret the IL-6 concentrations in the calf's serum and amniotic fluid, due to the lack of references in cattle, but the concentration in the dam's serum seems normal for this period (Ishikawa et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…We think that it is especially important for elimination of the fetal membrane and phylaxis after parturition to shift from T-helper 2-type (Th2) cell dominance to T-helper 1-type (Th1) cell dominance of T-helper cells in the intrauterine immune system around parturition. Ishikawa et al [17] and Nakada et al [18] demonstrated the changes in serum interleukin-6 (IL-6) and immunoglobulin isotypes (IgG1, IgG2) are important parameters of immunological function in dairy cattle. IL-6 is a cytokine mainly secreted by Th2 cells, immunoglobulin (Ig) G1 secretion from B cells is stimulated by activated Th2 cells, and IgG2 secretion from B cells is stimulated by activated Th1 cells [19].…”
Section: The Physiological Changes Occurring In Prepartum Dairy Cowsmentioning
confidence: 99%
“…IL-6 is a cytokine mainly secreted by Th2 cells, immunoglobulin (Ig) G1 secretion from B cells is stimulated by activated Th2 cells, and IgG2 secretion from B cells is stimulated by activated Th1 cells [19]. The peripheral concentrations of IL-6 before calving were higher than those after calving in dairy cattle [17]. Moreover, from 60 days before calving to calving the concentration of IgG1 decreases, while the concentration of IgG2 increases [18].…”
Section: The Physiological Changes Occurring In Prepartum Dairy Cowsmentioning
confidence: 99%
See 1 more Smart Citation